Para além do patológico: a contribuição da neurose obsessiva à compreensão do sintoma na psicanálise - Tresca, Christiane Santos (2022)
This document aims to study the neurotic symptom through a psychoanalytic approach. Due to the enormous theoretical and documentary richness, the Rat Man’s paradigmatic case was used as a guideline for this analysis. The theoretical contributions of Freud, Lacan and contemporary authors were discussed. From that, it was possible to apprehend the possibility of interpreting the symptomatic manifestation, both in its significant dimension and as a psychic conflict. In contrast, the medical-psychiatric guidelines about the symptom were considered in the discussion. Finally, it was concluded that categorizing the meaning of the symptom can limit the subject, distancing the subject from its truth. Psychoanalysis can stand as a resistance to this limitation